Endophthalmitis in Retinopathy of Prematurity after Intravitreal Aflibercept Injection. (22nd December 2020) - Suren, Elcin; Cetinkaya, Ersan; Kalayci, Mustafa; Özkan, Sariye Elif Özyazıcı; Kucuk, Mehmet Fatih; Erol, Muhammet Kazim
Abstract : We report the case of a male infant who had an intravitreal anti-VEGF (aflibercept) injection for the treatment of retinopathy of prematurity at 35-week postmenstrual age. Four days following the injection, retinal imaging demonstrated a yellowish gray blurred mass that extended into the vitreous in the right eye, and the vitreous body was blurred. After two days, despite starting endophthalmitis treatment, there was still no improvement in the retinal lesion. Due to the worsening of the clinical signs, we decided to perform 25-gauge lens-sparing pars plana vitrectomy.